Méthanisation, modernisation écologique et multifonctionnalité agricole : la diversité des trajectoires d’évolution - Paul Jutteau (Développement Durable et Territoires, 2024)
The German energy transition is an example of a policy of ecological modernisation, i.e. the ecological reform of the current economic and political system, whose modalities are studied by the eponym theory. This study combines ecological modernisation and agricultural multifunctionality and focus on one renewable energy, biogas and its implications for agriculture. The study of activity development trajectories in nearly 70 farms studied through comprehensive interviews with farmers will highlight the determining role of federal policies in these trajectories while explaining their diversity by the ability of actors to mobilize the different support instruments using their resources and those of the territory.